Perancangan Ikon Visual Dusun Plosokerep Melalui Pengembangan Motif Batik Daun Ploso sebagai Identitas Komunal - Ninggar Mayang Ningrum; Avierry Fionarizoca; Abdurrozaq (Jurnal Pengabdian Masyarakat Teknologi dan Pendidikan (MANTAP), 2026)
The community of Plosokerep Hamlet, Gondangrejo, Karanganyar, possesses a rich tradition of local performing arts but lacks a cohesive visual identity in the form of a signature village batik motif for ceremonial attire. This Community Service Program (PkM) aims to assist the community in designing a local visual icon based on native flora—specifically the leaves of the ploso tree (Butea monosperma)—leading to the creation of the "Ploso Joyo" batik motif. The methodology employed a participatory action approach involving sensing identification, visual stylization sketching, manual cap stamp crafting, and stamped batik production. The results demonstrate the establishment of a distinctive batik motif that has been successfully utilized for theatrical costumes, community event uniforms, and secured Copyright protection (HKI). This program effectively strengthens local empowerment and sustains community cultural identity.